Analysis of Product and Cultural Diversity as an Opportunity to Increase Market Expansion From Shocked Markets to E.Commerce at Masjid Al-Falah Surabaya - Noneng R.Sukatmadiredja; Emmywati; Iwang Suwangsih; Nuzulul Fatimah (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2021)
Analysis of product and cultural diversity as an opportunity to increase market expansion in shock markets towards E.Commerce at Masjid Al-Falah Surabaya